2013
DOI: 10.1371/journal.pone.0056747
|View full text |Cite
|
Sign up to set email alerts
|

Prior Infection Does Not Improve Survival against the Amphibian Disease Chytridiomycosis

Abstract: Many amphibians have declined globally due to introduction of the pathogenic fungus Batrachochytrium dendrobatidis (Bd). Hundreds of species, many in well-protected habitats, remain as small populations at risk of extinction. Currently the only proven conservation strategy is to maintain species in captivity to be reintroduced at a later date. However, methods to abate the disease in the wild are urgently needed so that reintroduced and wild animals can survive in the presence of Bd. Vaccination has been widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 44 publications
2
69
3
Order By: Relevance
“…The only previous study to repeatedly infect and clear amphibians of Bd seemed to conflict with our results 20 . In this study 20 , the authors concluded that there was no evidence of acquired resistance in the critically endangered booroolong frog ( Litoria booroolongensis ) because frogs previously cleared of Bd with the fungicide itraconazole did not have significantly lower prevalence or mortality upon re-infection than frogs that were not previously exposed to Bd or the fungicide (20 of 32 versus 14 of 28 infected, respectively; χ 2 1 = 0.9, P = 0.33).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The only previous study to repeatedly infect and clear amphibians of Bd seemed to conflict with our results 20 . In this study 20 , the authors concluded that there was no evidence of acquired resistance in the critically endangered booroolong frog ( Litoria booroolongensis ) because frogs previously cleared of Bd with the fungicide itraconazole did not have significantly lower prevalence or mortality upon re-infection than frogs that were not previously exposed to Bd or the fungicide (20 of 32 versus 14 of 28 infected, respectively; χ 2 1 = 0.9, P = 0.33).…”
contrasting
confidence: 99%
“…In this study 20 , the authors concluded that there was no evidence of acquired resistance in the critically endangered booroolong frog ( Litoria booroolongensis ) because frogs previously cleared of Bd with the fungicide itraconazole did not have significantly lower prevalence or mortality upon re-infection than frogs that were not previously exposed to Bd or the fungicide (20 of 32 versus 14 of 28 infected, respectively; χ 2 1 = 0.9, P = 0.33). However, the fungicide alone increased Bd prevalence in Bd -naive frogs (no previous fungicide: 14 of 28 infected, previous fungicide: 10 of 11 infected, χ 2 1 = 5.5, P = 0.01), consistent with other studies suggesting that itraconazole is immunosuppressive 27 .…”
mentioning
confidence: 72%
“…This corresponds to findings suggesting that infested waters and sand might be the primary source of infection [21,28,32]. Infections might also change due to within-host disease dynamics, modelled through transition probability rates between DOIs.…”
Section: Materials and Methods (A) Model Descriptionsupporting
confidence: 81%
“…For example, the yearly host survivorship is halved at a certain DOI tolerance level, T s and the adult breeding rate is halved at a certain DOI, T br . Individuals die immediately if their DOI reaches a lethal threshold [28,32,34]. We also explicitly considered the case where tadpoles completely tolerate their infections, e.g.…”
Section: Materials and Methods (A) Model Descriptionmentioning
confidence: 99%
“…Recently, Cashins et al (2013) used itraconazole (an antifungal) to clear frogs of their Bd infection and found that frogs infected with Bd, treated with itraconazole, and then re-exposed to Bd had a higher prevalence of infection compared to frogs only exposed to Bd once. Recently, Cashins et al (2013) used itraconazole (an antifungal) to clear frogs of their Bd infection and found that frogs infected with Bd, treated with itraconazole, and then re-exposed to Bd had a higher prevalence of infection compared to frogs only exposed to Bd once.…”
Section: Acquired Immunitymentioning
confidence: 99%